Influence of growth rate on minority carrier lifetime of multicrystalline silicon ingot. Issue 1 (October 2020) - Yang, Xiufan; Zhang, Dianxi; Guo, Zhongzheng; Yan, Wanjun; Zhang, Houyong
Abstract: Multicrystalline silicon was grown by directional solidification method, and different growth rates was obtained by optimizing the growth process. The influence of the growth rate on the minority carrier lifetime of the multicrystalline silicon ingot was studied. The results show that the infrared image of the middle and lower part of the silicon block with an average growth rate of 1.0cm/h has a lighter shade. The area with minority carrier lifetime of the silicon block is less than 4 us accounts for about 50%, and the average minority carrier lifetime is 5.28 us. Reduce the growth rate to 0.94cm/h, the infrared image of the crystal is pure and the crystal grains are coarse, the average minority carrier lifetime of the silicon block is increase to 5.65 us. When the growth rate is further reduced to 0.87cm/h, the crystal growth deviates from the vertical direction. The area of silicon block less than 4 us accounts for about 40%, and the average minority carrier lifetime is reduced to 5.39 us. The phase field method is used to calculate the growth of multicrystalline silicon. The results show that the greater the flow rate, the faster the growth of crystal nucleus and the easier the formation of competitive growth, which is in good agreement with the experiment.